The protective effects of Dendrobium nobile Lindl. alkaloids (DNLA) against CUMS-induced anxiety/depression and hippocampal transcriptome changes in rats - Ting-Wang Xiong; Bo Liu; Qin Wu; Yun-Yan Xu; Jie Liu; Jing-Shan Shi (Elsevier, 2023)
Introduction: Dendrobium is the famous Chinese medicine. Dendrobium nobile Lindl. alkaloids (DNLA) is the active ingredient and has been shown to have anti-aging, anti-Alzheimer's disease, and neuroprotective properties. This study examined effect of DNLA on chronic unpredictable mild stress (CUMS)-induced anxiety and depression in Fawn-Hooded (FH/Wjd) rats, a depression model in comorbid of alcoholism. Methods: FH/Wjd rats were subjected to CUMS for 49 days, followed by treatment with DNLA (20 mg/kg/day, po) for 35 days. The anxiety/depression behaviors, Nissl bodies, neurotransmitters and hypothalamic-pituitary-adrenal axis were examined. RNA-Seq analysis was performed to explore the protection mechanisms. Results: The CUMS-induced anxiety/depressive-like behaviors were ameliorated by DNLA in the elevated-plus-maze test, open-field test, and forced swimming test. The CUMS reduced Nissl bodies in the hippocampal CA2 region and cortex was alleviated by DNLA. CUMS disrupted 5-hydroxytryptamine, dopamine and gamma-aminobutyric acid in the brain, which were recovered by DNLA. Increases in serum adrenocorticotropic hormone and corticosterone levels were prevented by DNLA. RNA-Seq revealed CUMS-induced 1607 differentially expressed genes, which were ameliorated with DNLA treatment. KEGG showed the enrichment of Ribosome, Rap1 signaling, Tight junction, and RNA transport pathways. Discussion: FH/Wjd rats were susceptible to CUMS-induced anxiety and depression. DNLA ameliorated CUMS-induced anxiety/depression behaviors and neuronal damage. Multiple mechanisms were involved in the beneficial effects of DNLA, including neurotransmitters, the hypothalamic-pituitary-adrenal axis, and the hippocampal gene expressions.